Development of a Gamification-based Learning Model to Enhance Digital Creativity Competencies of Distance Learners - Amornrit, Phantipa; Bootchuy, Patthanan (ECT Education and Communication Technology Journal, 2025)
This research aimed to 1) examine expert opinions on a gamification-based learning model designed to enhance the digital creativity capabilities of distance learners, and 2) develop and evaluate this model. The research was conducted in two phases. Phase 1 involved studying the opinions of nine experts on theoretical concepts for designing and developing a gamification-based learning model to promote digital creativity among distance learners. Phase 2 focused on developing and evaluating the model to enhance the digital creative capabilities of distance learners. The research instruments included: 1) structured interviews with experts about the development approach of the gamification-based learning model to enhance students’ digital creativity capabilities, and 2) an evaluation form for assessing the model. Data were analyzed using mean, standard deviation, and content analysis. The results were as follows: 1) The gamification-based learning model consists of seven components: (1) content, objectives, missions, and learning activity outcomes, (2) gamification components, (3) strategies to promote digital creativity, (4) instructor components, (5) learner components, (6) learning systems, media, and technology, and (7) measurement and evaluation components. The learning management process includes three phases: First, the Pre-learning phase involves identifying learner characteristics, setting learning objectives, sequencing the structure of learning experiences, specifying necessary resources, tools, and technologies, and defining gamification components. Second, the During-learning phase consists of five sub-steps: (1) brainstorming and project ideation, (2) providing case studies and sharing ideas, (3) analyzing problems and synthesizing success factors for development, (4) extending and refining creative prototypes, and (5) presenting work for exchange and reflection. Third, the Conclusion phase involves measurement and evaluation through observing learner behaviors and development, evaluating digital creative outputs, assessing the ability to use digital tools for creative problem-solving, and gauging learner satisfaction. 2) The evaluation by five experts indicated that the overall quality of the gamification-based learning model was at the highest level (M = 4.82, SD = 0.41); specifically, the components and steps of the model were deemed highly appropriate (M = 4.84, SD = 0.37), and the gamification-based learning activities were also rated at the highest level of appropriateness (M = 4.85, SD = 0.36)